PENGUATAN PENDIDIKAN KARAKTER PEDULI SESAMA MELALUI KEGIATAN EKSTRAKURIKULER RELAWAN - Sani Muhamadi; Aan Hasanah (Jurnal Pendidikan Agama Islam, 2019)
The purpose of this study is to reveal the results of character building process in caring forothers through volunteer extracurricular activities. The method which is used is descriptive analyticalwith a qualitative approach. Data collection techniques are observation, interview and documentationstudies. Findings of this study: The process of strengthening character is carried out with routinetraining every week, monthly scheduled is cleaning river, mosques and the surrounding environment,and incidental activities to provide assistance to areas affected by natural and humanitarian disasters.The result is students show a stronger caring character. Supporting factors in strengthening thecharacter are the vision and mission and also goals of the madrasa, exemplary teachers and staff,activities carried out in schools, and involvement in community activities. While the obstruct factorsare the lack of funds to carry out activities, and the factor of parental permission in dissaster area.